The Student's Ability In Toeic At The Sixth Semester English Department Of STAI HUBBULWATHAN DURI - Susma S. Pradani; Setiawati; Dini Deswarni (DIMAR: Jurnal Pendidikan Islam, 2019)
The research aimed to find out measure the ability of students in answering Questions TOEIC on Sixth Semester, The TOEIC consists of two sections: Listening and Reading comprehension. Listening Comprehention (100 multiple-choice questions) and Reading (100 multiple-choice questions) and audiotape or VCD is used to test Listening Comprehension The TOEIC Listening and Reading comprehension test is an assessment of proficiency in English language as it is used in the global workplace, where English is the means of communication among both native and non-native speakers. The research population was Sixth Semester of STAI Hubbulwathan Duri in the academic year 2017/2018. The population of the research is 18 students. The sample technique is Total sampling. To perform the data, researcher used descriptive quantitative approach. Therefore, it related with statistic, so that researcher uses SPSS V. 17 to analyze the data. To make the reader easy to understanding this research, the data will be presented in tables and chart form. In order to investigate students’Ability in Mastering to Answer The Question TOEIC Test. After doing the research of students’Ability in mastering to Answer The Question TOEIC Test. researcher obtained the result of total mean score is 73.31 “Everage” category.